Frequent toothbrushing boosts resilience among children in poverty: results from a population-based longitudinal study - Ayako Suzuki; Yukako Tani; Aya Isumi; Takuya Ogawa; Keiji Moriyama; Takeo Fujiwara (BMC, 2024)
Abstract Background Poverty negatively impacts beneficial aspects of mental development, such as resilience. Toothbrushing, an oral health behavior, has the potential to protect children's resilience through its anti-inflammatory and self-management effects and may be more effective for children, especially children in poverty. This study investigated whether toothbrushing boosts resilience among children, especially children under poverty, and modifies the association between poverty and resilience using a longitudinal population sample of school children. Methods Data from the Adachi Child Health Impact of Living Difficulty (A-CHILD Study) were analyzed. A baseline study was conducted in 2015 in which the children were in first grade and followed through fourth grade (N = 3459, response rate: 80%, follow-up rate: 82%). Poverty was assessed by material deprivation (life-related deprivation and child-related deprivation) and annual household income at baseline. Children's toothbrushing frequency was assessed at baseline and classified into less than twice a day or twice or more a day. Children's resilience was assessed at baseline and follow-up using the Children's Resilient Coping Scale (range 0-100). Results Children who brushed their teeth twice or more a day in first grade had 3.50 points greater resilience scores in fourth grade than those who brushed their teeth less than twice a day in first grade. After adjusting for confounders, including resilience in first grade, among underpoverty children, those who brushed their teeth twice or more a day in first grade had higher resilience scores [2.66 (95% CI = 0.53, 4.79)] than those who brushed their teeth less than twice a day. Among nonpoverished children, toothbrushing frequency in first grade did not significantly correlate with resilience in fourth grade. Conclusions The beneficial effect of toothbrushing twice or more a day on resilience was more significant among children in poverty than among those without poverty in elementary school in Japan. Health policy focused on frequent toothbrushing may contribute to boosting resilience among children living in poverty.